2015
DOI: 10.1186/s40711-015-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Policy entrepreneur and social policy innovation in China

Abstract: Fostering policy innovation at the local level and spreading the successful practice have been pervasive features of policy making in postreform China. The existing literature explains why the local government launches innovations and what enables these innovations. However, little research has been done on the emerging process of the new ideas and the process in which new policies are accepted by stakeholders. This article is an case study based on the policy innovation in the health insurance system in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Since experimentalist governance offers more spaces for bureaucratic discretion than law-based democracies (Heilmann, 2008), policy entrepreneurs– bureaucrats who want to try novel approaches–became critical (Teets, 2015; Zhu and Xiao, 2015). Under the experimentation regime, policy entrepreneurs at the national level have to secure permission and resources from higher leaders to set up local pilot sites to demonstrate the effectiveness of their approach.…”
Section: Introductionmentioning
confidence: 99%
“…Since experimentalist governance offers more spaces for bureaucratic discretion than law-based democracies (Heilmann, 2008), policy entrepreneurs– bureaucrats who want to try novel approaches–became critical (Teets, 2015; Zhu and Xiao, 2015). Under the experimentation regime, policy entrepreneurs at the national level have to secure permission and resources from higher leaders to set up local pilot sites to demonstrate the effectiveness of their approach.…”
Section: Introductionmentioning
confidence: 99%
“…The mushrooming scholarship of the past decade has found that authoritarian states deliver 9 Ngok andHuang 2014. 10 Zhu, Yapeng, andXiao 2015;Zhu, Xufeng, and Zhao 2018;He 2018. 11 Encouraged by the operation of dibao in the cities, from 2004 the Chinese government started to roll out a similar programme in the countryside.…”
Section: The Political Economy Of Social Policymaking In Chinamentioning
confidence: 99%
“…Previous works demonstrate that the bottom-up diffusion of successful government practices from local to central government is a pervasive feature of Chinese policymaking (Hammond, 2013; Zhu, 2012, 2013). These studies focus on issue areas such as urban income policy (Hammond, 2013), local housing (Zhu, 2012), and municipal health insurance systems (Zhu and Xiao, 2015). As these policy areas are inherently regional in nature, policy entrepreneurship from local governments is thus hardly surprising.…”
Section: Toward a Conception Of State-led Gfnsmentioning
confidence: 99%